New life forms on the Web: Library mashups - Serrano-Cobos, Jorge (Anuario ThinkEPI, 2008)
This insightful introduction to understanding mashups describes them as a kind of content aggregation that permits mixing several information sources or applications, in an effort to develop different content or application based on these sources, saving time and development effort. Some real examples and advantages are pointed out, as well as possible implications for future Opacs, within the world of the so-called "Library 2.0".